2007
DOI: 10.1097/00124784-200701000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Workforce Enumeration

Abstract: The most common source of information on workforce in the United States is the Bureau of Labor Statistics (BLS), a branch of the Department of Labor. In 1998, 14 public health workforce titles were added to the BLS Standard Occupational Classification (SOC) system. While this was a constructive step, it is not a "quick fix," because these additional titles do not solve the longstanding problems inherent in capturing accurate PH workforce data. As is true for all currently available sources, BLS statistics capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…A major concern, however, is that most rural PHNs' highest level of nursing education is the associate degree level, which typically does not include any curricular content in public health. In addition, the public health nursing workforce is aging and retiring at rapid rates, creating serious workforce concerns, especially in rural and frontier areas, where recruitment and retention of well‐prepared nurses has historically been challenging (Gebbie, 2000). In a study of the public health systems in Idaho and Wyoming conducted in 1998–1999, Richardson, Casey, and Rosenblatt (1999) found that Idaho had 39 public health professionals per 100,000 people, over half of whom were nurses, and most of these nurses did not have formal preparation in public health.…”
Section: Introductionmentioning
confidence: 99%
“…A major concern, however, is that most rural PHNs' highest level of nursing education is the associate degree level, which typically does not include any curricular content in public health. In addition, the public health nursing workforce is aging and retiring at rapid rates, creating serious workforce concerns, especially in rural and frontier areas, where recruitment and retention of well‐prepared nurses has historically been challenging (Gebbie, 2000). In a study of the public health systems in Idaho and Wyoming conducted in 1998–1999, Richardson, Casey, and Rosenblatt (1999) found that Idaho had 39 public health professionals per 100,000 people, over half of whom were nurses, and most of these nurses did not have formal preparation in public health.…”
Section: Introductionmentioning
confidence: 99%
“…Database and World Wide Web searches were conducted to identify established documents describing PH practice using terms such as “practice,”“process,” and “work.” Such documentation is not well represented in indexed sources (Turner et al 2009); therefore, the document search relied on the research team's familiarity with the domain (Gebbie and Hwang 1998; Gebbie and Rice 1998; Gebbie 1999a, b; Gebbie and Garfield 2001; Gebbie and Merrill 2001, 2002; Gebbie et al 2002a, 2003, 2007; Gebbie, Merrill, and Tilson 2002b; Merrill et al 2003; Merrill 2004; J. Merrill and K. M. Gebbie, unpublished data) and previous taxonomy work (Gebbie and Merrill 2001). Most documents were retrieved from websites of professional associations and other organizations representing the practice community.…”
Section: Methodsmentioning
confidence: 99%
“…• The IOM (UNH 2003) which recommended that "all undergraduates should have access to education in public health" (p. 144) • The public health workforce in New Hampshire which is enumerated at 83 governmental public health workers per 100,000 population compared to an average of 118 governmental public health workers per 100,000 for other New England states (Gebbie 2000) The UNH MPH Program is a nonresidential graduate program administered by the Department of Health Management and Policy (HMP) in the College of Health and Human Services on the main campus in Durham, New Hampshire ( Fig. 3.1).…”
Section: University Of New Hampshire Master Of Public Health Programmentioning
confidence: 99%